Karyological Investigate on Some Taxon of Naturally Growing in Turkey - Gedik, Osman; Kursat, Murat; Kiran, Yasar; Karatas, Mizbah (Kahramanmaras Sutcu Imam Univ Rektorlugu, 2016)
In this study; the somatic chromosome numbers and detailed morphometric properties of some taxa distributed in Turkey were examined. C. montanum belonging to the genus Chrysophthalmum, L. nervosum belonging to the genus Linum, endemic S. orientalis subsp. bicolor belonging to the genus Scutellaria, N. macrosiphon, N. trachonitica and N. racemosa belonging to genus Nepeta were investigated using karyological techniques. Diploid chromosome numbers were found to be N. macrosiphon, N. racemosa 2n=16, C. montanum, N. trachonitica 2n=18, S. orientalis subsp. bicolor 2n=22 ve L. nervosum 2n=54 in this taxa. Chromosomes sustained median region (m) and submedian (sm) centromers. A pair of satellite chromosomes (sat-chromosome) was observed in N. macrosiphon. and secondary structures was observed in N. racemosa.
Keywords: Chrysophthalmum; Linum; Scutellaria; Nepeta; Chromosome numbers; karyotype